2020
DOI: 10.7554/elife.54224
|View full text |Cite
|
Sign up to set email alerts
|

Presynaptic PTPσ regulates postsynaptic NMDA receptor function through direct adhesion-independent mechanisms

Abstract: Synaptic adhesion molecules regulate synapse development and function. However, whether and how presynaptic adhesion molecules regulate postsynaptic NMDAR function remains largely unclear. Presynaptic LAR family receptor tyrosine phosphatases (LAR-RPTPs) regulate synapse development through mechanisms that include trans-synaptic adhesion; however, whether they regulate postsynaptic receptor functions remains unknown. Here we report that presynaptic PTPσ, a LAR-RPTP, enhances postsynaptic NMDA receptor (NMDAR) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 89 publications
1
27
0
Order By: Relevance
“…Previous KO mouse studies have revealed the importance of LAR-RPTPs for synaptic and cognitive function. Specifically, PTPσ KO decreases presynaptic release probability and NMDAR-dependent LTP in the hippocampal Schaffer-CA1 synapses and abnormally enhances novel object recognition (Horn et al, 2012 ; Han et al, 2020a ; Kim et al, 2020 ). In contrast, a previous study by Uetani et al ( 2000 ) showed that PTPδ KO increases release probability and LTP in the same type of synapses and impairs spatial learning and memory.…”
Section: Lar-rptp-based Synaptic Organizing Complexesmentioning
confidence: 99%
“…Previous KO mouse studies have revealed the importance of LAR-RPTPs for synaptic and cognitive function. Specifically, PTPσ KO decreases presynaptic release probability and NMDAR-dependent LTP in the hippocampal Schaffer-CA1 synapses and abnormally enhances novel object recognition (Horn et al, 2012 ; Han et al, 2020a ; Kim et al, 2020 ). In contrast, a previous study by Uetani et al ( 2000 ) showed that PTPδ KO increases release probability and LTP in the same type of synapses and impairs spatial learning and memory.…”
Section: Lar-rptp-based Synaptic Organizing Complexesmentioning
confidence: 99%
“…PTPσ deficiency also increases frequency but reduces efficiency of excitatory postsynaptic currents (Horn et al, 2012;Han et al, 2020) and impairs long-term potentiation (LTP) (Horn et al, 2012). LTP deficits were also observed when PTPσ knockdown was restricted to excitatory cortical and hippocampal neurons (Kim et al, 2020). Similarly, overexpression TRKB in pyramidal neurons, which increases TRKB phosphorylation and signaling through PLCγ1, also impairs LTP (Koponen et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, overexpression TRKB in pyramidal neurons, which increases TRKB phosphorylation and signaling through PLCγ1, also impairs LTP (Koponen et al, 2004). Interestingly, Kim et al showed that presynaptic PTPσ deficiency selectively impairs NMDA-dependent postsynaptic currents, and it happens through a mechanism independent of PTPσ trans-synaptic adhesion, suggesting further involvement of PTPσ cytoplasmic phosphatase domains in this process (Kim et al, 2020). Even though direct relationship between LTP and memory remains to be a subject to debate (Stevens, 1998;Nicoll, 2017), NMDA-dependent LTP is known to be critical for normal memory performance, and disturbances in this pathway impair memory function (Nakazawa et al, 2004;Li and Tsien, 2009;Morris, 2013;Nabavi et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…For the brain to operate properly, the synapses that make up the neural circuits must work well [21]. The major adhesion protein PTPσ is found in specific neural circuits in the hippocampus and is known to mediate memory and regulate function by helping localize and stabilize NMDA receptors [22]. Synapses can continuously change their structure and function according to their activities and play an important role in memory formation [23].…”
Section: Human Brain and Its Function: Memory Formation In The Neural Networkmentioning
confidence: 99%